Distribution and behaviour of rock glaciers in the Adamello-Presanella Massif (Italian Alps) - BARONI, CARLO; CARTON A; SEPPI R. (Permafrost and Periglacial Processes, 2004)
An inventory of rock glaciers in the Adamello–Presanella Group is presented. The distribution, behaviour and morphological characteristics of rock glaciers are described and organized in a GIS. Furthermore, we analyse the relationship between rock glaciers and vegetation and tentatively discuss that between rock glacier distribution and climatic parameters. A total of 216 rock glaciers have been identified: 41% (n1⁄488) are active/inactive (sensu Barsch) and the rest are relict. There is a difference of about 430m in elevation between the fronts of active/inactive forms and those of relict forms. In the group of active/inactive rock glaciers, 59 are considered active and some of these are certainly in motion, as confirmed by two topographic surveys. At least 30 rock glaciers have developed since the Little Ice Age. The mean elevation of the fronts of active rock glaciers (2527 m) lies well below the estimated altitude of isotherms 1C (2740 m) and 2C (2910 m), suggesting that the reconstructed MAAT of 1/2C does not coincide with local MAAT in the entire group or that the studied rock glaciers are in disequilibrium with respect to current climatic conditions in the area. In conclusion, we must be cautious in using the regional MAAT for identifying active forms and in utilizing the position of rock glacier fronts for reconstructing the regional MAAT.